Pengelolaan Program KB Nasional di Dki Jakarta Tahun 2014 - Menara Simanjuntak; Haryadi Sarjono; Iwan Zulkifli (Binus Business Review, 2014)
Research of the National Family Planning Program Management in Jakarta is the follow-up study that analyzes the role of the relationship manager / executive of Family Planning, the availability of caunsellor and cadres as well as the readiness of Family Planning services to the dependent variable. Dependet variable is the interaction of the managers/implementers Family Planning to the achievement of family planning program in Jakarta. The purpose of this study was to obtain analytical results in the relationship of important variables in the management of family planning programs in Jakarta as a basis for priority activities proposed in the action plan of the family planning program in Jakarta. This study uses quantitative analysis with the technic of achieving sample by stratified random sampling, with a total sample of 198 respondents from the Provincial, Municipal and District Level. After the research team analyzes the results of the regression relationships of variables to provide conclusions and recommendations as an attempt to formulate strategic activities in the implementation of the National Family Planning Program in Jakarta. It can be concluded that there is influence and significant simultaneous relationship between the role of managing/implementing family planning programs and the readiness of Family Planning services in their effort to the success of family planning programs in Jakarta. Based on the results of quantitative data processing of the regression equation with the interpretation output LISREL with the value of R square of 0.493 or 49.3 percent.